Beyond Infections: New Warning Signs for Inborn Errors of Immunity in Children - Costagliola, Giorgio; Peroni, Diego G.; Consolini, Rita (Frontiers in Pediatrics, 2022)
Patients with inborn errors of immunity (IEI) are susceptible to developing a severe infection-related clinical phenotype, but the clinical consequences of immune dysregulation, expressed with autoimmunity, atopy, and lymphoproliferation could represent the first sign in a significant percentage of patients. Therefore, during the diagnostic work-up patients with IEI are frequently addressed to different specialists, including endocrinologists, rheumatologists, and allergologists, often resulting in a delayed diagnosis. In this paper, the most relevant non-infectious manifestations of IEI are discussed. Particularly, we will focus on the potential presentation of IEI with autoimmune cytopenia, non-malignant lymphoproliferation, severe eczema or erythroderma, autoimmune endocrinopathy, enteropathy, and rheumatologic manifestations, including vasculitis and systemic lupus erythematosus. This paper aims to identify new warning signs to suspect IEI and help in the identification of patients presenting with atypical/non-infectious manifestations.